Pleiotropic effect of teneligliptin versus glimepiride add-on therapy on hs-CRP and cardiorenal parameters in Indian type 2 diabetes patients: An open-labeled randomized controlled trial - M Kanimozhi; Manisha Bisht; Ravikant; Arkapal Bandyopadhyay; Manisha Naithani; Shailendra Handu (Perspectives in Clinical Research)
Objective: The objective of the study was to estimate the pleiotropic effect of teneligliptin on high-sensitivity C-reactive protein (hs-CRP) levels and some cardiorenal parameters in comparison to glimepiride, both as add-on therapy to metformin. Methodology: This 12-week open-label, parallel-group, randomized controlled trial was conducted among Indian people with type 2 diabetes mellitus and on metformin monotherapy with poor glycemic control (glycated hemoglobin >7% or 53 mmol/mol). The endpoints were mean change in hs-CRP levels, systolic blood pressure (SBP), diastolic blood pressure (DBP), serum creatinine, blood urea, estimated glomerular filtration rate (eGFR), and change in cardiovascular (CV) risk categories from baseline to end of 12 weeks. Results: Seventy participants were randomized (1:1) to receive either teneligliptin 20 mg once daily (n = 35) or glimepiride 1 mg twice daily (BD) (n = 35) as an add-on to metformin 500 mg BD. The mean age of the participants was 50.65 and 50.7 years in arms 1 and 2, respectively. At 12-weeks end, teneligliptin add-on caused a statistically significant reduction in hs-CRP compared to glimepiride in both per-protocol (PP) and intention-to-treat (ITT) sets. No significant difference was observed for changes in SBP and DBP, creatinine, urea, eGFR levels, and CV risk category in both PP and ITT sets. Conclusion: Teneligliptin add-on resulted in favorable effects on hs-CRP levels and comparable effects on cardiorenal parameters compared to glimepiride add-on therapy at 12-weeks end. This trial has been prospectively registered in CTRI (Clinical Trials Registry of India). Registration number: CTRI/2021/08/035342.